The Influence of Environmental Management Accounting and Environmental Performance on Company Value with Environmental Disclosure as an Intervening Variable: Manufacturing Companies in the Food and Beverage Subsector Listed on the IDX for the 2023 Period - Abas, Muhammad Rizal; Jamali, Hisnol; Amin, Asbi (SIMAK, 2025)
This study aims to determine and test the effect of environmental management accounting and environmental performance on company value by using environmental disclosure as an intervening variable in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2023 period. Data collection utilizes secondary data obtained from financial reports and sustainability reports accessed through www.idx.co.id specifically within manufacturing companies in the consumer goods industry sector using a purposive sampling technique. The population is 95 food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange. With samples taken as many as 38 observation samples, with the analysis tool using smartpls.4. The results of the study indicate that environmental management accounting has a negative and insignificant effect on company value, environmental performance has a negative and insignificant effect on company value, environmental management accounting has a negative and insignificant effect on environmental disclosure, environmental performance has a positive and significant effect on environmental disclosure, environmental disclosure has a positive and insignificant effect on company value, environmental disclosure cannot be a mediating variable.